Modeling, transient simulations and parametric studies of parabolic trough collectors with thermal energy storage. (15th March 2020) - Akba, Tufan; Baker, Derek; Yazıcıoğlu, Almıla Güvenç
Highlights: Component based solar power plant control allow controlling numerous working modes. Solar power plants changes quadratic at same cost when storage size changes. Optimum plant design responds linearly with investment cost up to 60% of demand. Distributing the load to whole daytime allows the highest dispatchability. 24-h load dispatched better than high input time (10:00–14:00). Abstract: For investigating the system response of parabolic trough collector heat generating system, a plant with parabolic trough collector field and two-tank molten salt thermal energy storage model with component-level control algorithm is developed for managing various working conditions. The model is transient inside the components and responds with hourly weather and demand data. The main purpose of this work is providing an alternative design methodology that focuses on the collector field, and storage size by investment, location, and load type. Using a simple economic model, the plant parameters are calculated, which contains only initial investment costs of the parabolic trough collector field and thermal energy storage costs. Depending on the economic model, various sizes of collector field and storage combinations are created at fixed initial investment costs in the mathematical model. A parametric study is performed by using the economic model simulating at several initial investment costs, two different locations in Turkey, and four different load profiles. As a result of the parametric study, maximum solar fraction cases are selected and the generalized trend is observed. The effect of thermal energy storage on the solar fraction is discussed and the change in thermal energy storage with optimum plant size is investigated. After the optimum investment, the linear increment trend of dispatchability is disappearing and increases asymptotically by increasing the plant and/or storage size. Later in this work, the significance of the load profile is emphasized, which should be one of the major design parameters for solar-powered energy systems.